Watchful Lives in the U.S.-Mexico Borderlands - Whittaker, Catherine (Vigilanzkulturen / Cultures of Vigilance, 2023)
The book shows how Chicanx, Latinx and otherwise watched and "othered" people in San Diego, close to the US-Mexico border, respond to racism and surveillance. Watchfulness goes beyond counter-surveillance, as it is understood as a "way of life" and contributing to community building. The contributions pay attention to notions of borderlands, coloniality, subjectivity, struggle, the racialized body and the digital sphere.